Fissure sealants: A review of their importance in preventive dentistry - Veiga, Nélio J. (2015)
Background: For the prevention of dental caries, fissure sealants application is recommended if pits and fissures are very deep and narrow, creating a physical barrier for the plaque's accumulation, in these specific anatomical areas of the tooth. Aim: This review article about fissure sealant aims to address the main properties, indications, advantages and limitations of fissure sealants that are used in order to acquire a higher level of knowledge about what is known today about this biomaterial and how and when it should be applied by clinicians. Review Results: Studies have shown that fissure sealants applied both in clinics and in schools, are highly effective in preventing dental caries, reducing caries in pits and fissures up to 60% for 2 to 5 years after its implementation. The application of fissure sealants has specific indications, such as: newly erupted teeth, with deep fissures and clinically free of dental caries; patients who present physical and mental disabilities; adult patients that are under medical treatment that involves a significant decrease of the salivary flow. Several studies analyzed do not clarify which type of fissure sealant, if a resin-based or glass ionomeric fissure sealant, has higher retention rate and effectiveness. Conclusion: The application of sealants is a recommended procedure to prevent or control dental caries. However, the relative effectiveness of different types of sealants has yet to be established. Clinical Significance: Fissure sealants are recommended to be applied soon after tooth eruption, mainly at the level of the first permanent molars. However, health professionals should always take into account that fissure sealants, currently used, have limitations such as microleakage. Regular reassessment, in order to avoid the development of dental caries, on teeth with partial or total loss of fissure sealants is recommended.